Real-time patient’s vital sign monitoring using ESP32 - Anuar, Nur Farahdinna; Rahmat, Mohammad Hafidz; Mohd Supir, Mohd Hafifi (College of Computing, Informatics, and Mathematics, 2025)
The IoT technology in remote patient monitoring (RPM) allows healthcare enhancement through live vital sign monitoring. A realtime patient monitoring system based on ESP32 platform and ThingSpeak platform and Telegram bots and mobile application is introduced in this research. The system operates continuously to acquire heart rate data and SpO2 readings and temperature measurements after which the data gets sent to the cloud for both analysis and visualization. The mobile app shows current healthcare data immediately while Telegram bots send out immediate notice updates. The system operates effectively based on functionality and network performance verification results. Upcoming enhancements in the system involve GPS tracking capabilities along with improved encryption measures and extra sensors for expanding healthcare monitoring features.